Clinical examples of the use of allogeneic platelet-rich plasma for the treatment of thermal skin burns in children - N. M. Shapetska; M. P. Potapnev; Yu. G. Degtyarev; I. N. Zelianko (Acta Biomedica Scientifica)
It is quite difficult to determine both the method and timing of healing of a burn wound in children at the initial stages of treatment and during a visual clinical examination. In the treatment of thermal burns in children, preference is given to conservative methods, although they do not always lead to optimal healing of the burn. The use of PRP (platelet-rich plasma) in the treatment of burn wounds can have a beneficial effect on the timing and quality of healing of burned skin. Also, in certain cases, it allows to avoid surgical intervention in order to restore damaged skin or helps to reduce the volume and number of surgical operations when there is a shortage of donor resources. We present three clinical cases of using allogeneic PRP for the treatment of thermal burns of different etiologies (flame, hot liquid, contact). The use of PRP of the allogeneic type is due to the fact that children with burn injuries have limitations and contraindications to the use of autologous PRP. Allogeneic PRP and its use allow to reduce the time of epithelization of burn wounds of IIIAB degree (2–3 degrees according to ICD-10) and in some cases avoid surgical intervention to restore damaged skin. Its main advantages are good tolerability, relative availability, absence of contraindications and ease of use. Presented clinical examples for the first time clearly demonstrate the high effectiveness of allogeneic PRP in the treatment of thermal burns of different etiologies in children.